DESCRIPTION OF NOISE IN THE COMPRESSOR AND GENERATOR AREA AT PT PERTAMINA EP ASSET 3 TAMBUN FIELD – BEKASI - Marfiana, Pipit (Journal of Green Science and Technology, 2023)
PT Pertamina EP Asset 3 Tambun Field is a state-owned company engaged in Production Exploration, in the process this company has tools that must pay attention to the noise level, namely Compressors and Gensets. Compressors and generators are very influential on hearing loss in workers, therefore efforts to prevent hearing loss must be carried out. The objectives to be known are to know the noise conservation program, Standard Operating Procedures (SOP) in implementing noise conservation, and Implementation of Noise Conservation in Compressor and Genset Areas. This research method uses direct observation, interviews and literature studies. The results show that the Hearing Conservation Program has 7 (seven) components, namely: noise exposure survey, noise control, worker training, personal protective equipment, audiometric examination, recording and reporting, program assessment. The procedure used refers to the Individual Work Procedure (TKI) for Noise Measurement. The implementation of the Noise Measurement Program is carried out by the contractor once every 1 (one) year or every time there is a process change or a new tool. The Hearing Conservation Program must continue to make continuous improvements. It should be noted in monitoring workers in the Genset and Compressor area so that workers always use hearing protection equipment.